EFFECT OF HIGH- AND LOW-TEMPERATURE STRESS ON THE METABOLOME OF N. SIBIRICA PALL. AND NITRARIA SCHOBERI L. MICROCLONES IN VITRO - Zorbekova, Aigerim; Terletskaya, N.V.; Korbozova, N.K.; Dayyrbekova, D.; Kudrina, N.O.; Mamirova, A.; Ashimuly, K.; Shadenova, E.A. (Eurasian Journal of Applied Biotechnology, 2025)
The results of an in vitro study of the effects of high temperature and cold stress on the metabolome of N. sibirica Pall. and Nitraria schoberi L. microclones are presented. Gas chromatography–mass spectrometry (GC–MS) analysis revealed significant stress-induced changes in the metabolome spectra of the studied species. These results are important for the development of metabolomics and for improving our understanding of plant responses to abiotic stress factors. Furthermore, the study’s results help determine the role of individual metabolites in these processes, which is important for developing strategies for the targeted induction of valuable secondary metabolites in vitro.